NUTRITIONAL VALUE AND HEAVY METALS CONTENTS OF THE DRIED SEA CUCUMBER Stichopus vastus FROM SALEMO ISLAND, INDONESIA - Abdullah Rasyid (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
The dried sea cucumber Stichopus vastus is one of the commercially species harvested in Indonesian waters. This study aims to highlight the nutritional value and heavy metals content of dried sea cucumber S. vastus. Proximate (moisture, ash, protein, fat and carbohydrate), mineral (sodium, calcium, potassium and iron) and heavy metal (mercury, cadmium, arsenic and lead) were determined by standard method of AOAC, while phosphorous was determined by spectrophotometric method. Chondroitin sulphate was determined by UPLC method, glucosamine sulphate and vitamin (A, B1, B2 and E) by HPLC method. Results show that protein was the major component in proximate analysis of dried sea cucumber S. vastus in the present study. The protein content was 38.70%. Moisture, ash, fat and carbohydrate content were 19.46%, 34.04%, 0.38% and 7.42% respectively. All vitamins and heavy metals examined in this study were not detected. The sodium content was 8054.36 mg/100 g higher than other minerals. Calcium, potassium, phosphorus and iron content were 2449.9 mg/100 g, 159.77 mg/100 g, 5085.2 mg/100 g and 520.8 mg/100 g respectively. Glucosamine sulphate content was found to be 2.429 g/100 g, whereas chondroitin sulphate was found to be 1.115 g/100 g. It can therefore, be concluded that the dried sea cucumber S. vastus from Salemo Island is safe for human consumption and hence can be used as a source of food supplement in the future. Keywords: food supplement, Salemo island, Stichopus vastus